2010
DOI: 10.1175/2009jhm1169.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Scale Relationships of Uncertainty Propagation of Satellite Rainfall through a Distributed Hydrologic Model

Abstract: The study presents a data-based numerical experiment performed to understand the scale relationships of the error propagation of satellite rainfall for flood evaluation applications in complex terrain basins. A satellite rainfall error model is devised to generate rainfall ensembles based on two satellite products with different retrieval accuracies and space–time resolutions. The generated ensembles are propagated through a distributed physics-based hydrologic model to simulate the rainfall–runoff processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 39 publications
8
86
0
3
Order By: Relevance
“…The APHRODITE, PERSIANN, and GSMAP products are seldom evaluated in northeast China using basin-scale gauge data (Zhou et al, 2008). Owing to the high heterogeneity of rainfall across a variety of spatiotemporal scales, the uncertainty characteristics of precipitation products are variable (Asadullah et al, 2008;Dinku et al, 2008;Nikolopoulos et al, 2010;Pan et al, 2010). Thus, in northeast China, it is essential to completely evaluate the applicability of these precipitation products.…”
Section: W Qi Et Al: Evaluation Of Global Fine-resolution Precipitamentioning
confidence: 99%
“…The APHRODITE, PERSIANN, and GSMAP products are seldom evaluated in northeast China using basin-scale gauge data (Zhou et al, 2008). Owing to the high heterogeneity of rainfall across a variety of spatiotemporal scales, the uncertainty characteristics of precipitation products are variable (Asadullah et al, 2008;Dinku et al, 2008;Nikolopoulos et al, 2010;Pan et al, 2010). Thus, in northeast China, it is essential to completely evaluate the applicability of these precipitation products.…”
Section: W Qi Et Al: Evaluation Of Global Fine-resolution Precipitamentioning
confidence: 99%
“…Neste trabalho foi possível avaliar o modelo de propagação de erro SREM2D e concluir que este modelo possui potencial para gerar campos realísticos de precipitação para bacias de grande porte, complementando os estudos de Maggioni et al (2013) e Nikolopoulos et al (2010), aplicados a bacias de pequeno porte.…”
Section: Conclusõesunclassified
“…Less testing has been undertaken in smaller catchments (less than 100 km 2 ). Nikolopoulos et al (2010) showed that the error propagation from satellite rainfall estimates to a hydrological model is dependent on the catchment scale: in small-scale applications, product resolution becomes a critical issue. Even though the spatial resolution is relatively coarse compared to the scale of the studied catchments, this open-source dataset provided the most precise available rainfall representation in terms of temporal resolution.…”
Section: Rainfall Data and Spatial Modellingmentioning
confidence: 99%
“…Satellite and radar-borne rainfall data are increasingly used in regions where gauging networks are insufficient (Hong et al 2007;Nikolopoulos et al 2010). Remotely sensed data may provide spatially distributed rainfall estimates for often inaccessible catchment areas (Nikolopoulos et al 2010) that can prove more effective in capturing the spatial and temporal variability in rainfall than point gauges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation